2019
DOI: 10.5326/jaaha-ms-6904
|View full text |Cite
|
Sign up to set email alerts
|

Combination Anthelmintic Treatment for Persistent Ancylostoma caninum Ova Shedding in Greyhounds

Abstract: Ancylostoma caninum is a nematode of the canine gastrointestinal tract commonly referred to as hookworm. This study involved eight privately owned adult greyhounds presenting with persistent A. caninum ova shedding despite previous deworming treatments. The dogs received a combination treatment protocol comprising topical moxidectin, followed by pyrantel/febantel/praziquantel within 24 hr. At 7–10 days posttreatment, a fecal examination monitored for parasite ova. Dogs remained on the monthly combination treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…In the present study, more than 15% of dogs visiting dog parks in the Southeast, and 4 to 5.3% of those in the Midwest and Northeast, were infected with hookworm, a finding that is particularly concerning given the recent reports of multiple drug-resistant hookworms in pet dogs, including Greyhounds [33][34][35]. Although we do not know the resistance status, six of the 12 Greyhounds sampled from dog parks in the present study were positive for hookworm, and five of those six were reported by the owner to be on a HWCM at the time they were sampled, compared to 57.7% of non-Greyhound, hookworm positive dogs that were reportedly receiving a HWCM (data not shown).…”
Section: Discussionmentioning
confidence: 40%
“…In the present study, more than 15% of dogs visiting dog parks in the Southeast, and 4 to 5.3% of those in the Midwest and Northeast, were infected with hookworm, a finding that is particularly concerning given the recent reports of multiple drug-resistant hookworms in pet dogs, including Greyhounds [33][34][35]. Although we do not know the resistance status, six of the 12 Greyhounds sampled from dog parks in the present study were positive for hookworm, and five of those six were reported by the owner to be on a HWCM at the time they were sampled, compared to 57.7% of non-Greyhound, hookworm positive dogs that were reportedly receiving a HWCM (data not shown).…”
Section: Discussionmentioning
confidence: 40%
“…In the present study, more than 15% of dogs visiting dog parks in the Southeast, and 4 to 5.3% of those in the Midwest and Northeast, were infected with hookworm, a nding that is particularly concerning given the recent reports of multiple drug-resistant hookworms in pet dogs, including Greyhounds [33][34][35]. Although we do not know the resistance status, six of the 12 Greyhounds sampled from dog parks in the present study were positive for hookworm, and ve of those six were reported by the owner to be on a HWCM at the time they were sampled, compared to 57.7% of non-Greyhound, hookworm positive dogs that were reportedly receiving a HWCM (data not shown).…”
Section: Discussionmentioning
confidence: 45%
“…This is an important and concerning development, as the emergence and spread of MDR A. caninum to all three major anthelmintic classes, would pose a serious threat to canine health, as there are no other effective drug classes currently approved for the treatment of hookworms in dogs in the USA. Although a recent study reported success in treating several cases of recurrent hookworm infections in greyhounds recently retired from racetracks using a combination therapy of moxidectin, pyrantel pamoate and febantel at monthly intervals [89], we have recently diagnosed multiple cases at a greyhound adoption kennel where this same regimen appears to be ineffective (data not shown). The disparity in these findings is consistent with the rapid evolution of moxidectin resistance when moxidectin is used against ivermectin resistant worms [61].…”
Section: Discussionmentioning
confidence: 96%